Tanggung Jawab Hukum Berdasarkan Pasal 1365 KUH Perdata Terhadap Tertanggung yang Mengalami Kerugian Dalam Kasus Gagal Bayar Asuransi Jiwa - Widananti, Agnes (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article aims to identify the provisions of legislation regarding legal liability for life insurance insureds as well as legal responsibility based on Article 1365 of the Civil Code for insureds who suffer losses in cases of failure to pay life insurance. This research is normative juridical research which uses primary materials in the form of statutory regulations with a conceptual approach and secondary data obtained through literature studies consisting of books, journal articles and internet sites. The results of this research are the importance of an insurance policy as written evidence to request compensation due to non-fulfillment of contractual obligations in a life insurance agreement and based on Article 1365 of the Civil Code, the insurer is obliged to carry out legal liability due to their fault by compensating the insured for losses in cases of life insurance failure to pay.